ANALISIS KESALAHAN PENGGUNAAN HURUF KAPITAL DAN TANDA BACAPADA RINGKASAN SKRIPSI PROGRAM STUDI PGSD ANGKATAN 2012 - Sari, Hidayah; Kurniaman, Otang; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The error of spelling look simple, but will affect the quality of writing and understanding of someone language. If observed carefully, students still make eror in writing thesis, whether it is the use of capital letters or punctuation, especially in the thesis summary. The purpose of this research is to describe the error of capital letters and punctuation and what errors often arise. The method used is descriptive quantitative with sample of 54 summary thesis of PGSD study programs force 2012. Based on the result of research, the highest capitalization error at the beginning of sentence (48,15%) in 26 summaries and the lowest on the kinship indicator in the salary (1, 85%) in 1 summary, while the highest error on the use of punctuation, that is in the semicolon behind the link (50%) in 27 summaries and the lowest on the use of commas to separate equivalent sentences, dots at the end of the complete statement, hyphen, and quotation marks (1.85%) in 1 summary thesis. Aspects that often arise are the capital letters in the beginning of the sentence as much as 48 times and the error on the comma between the details as much as 62 times.Key words: Error analysis, capitalization, punctuation